Examining “Salami slicing” publications as a side-effect of research performance evaluation: An empirical study - D’Angelo Ciriaco Andrea (Journal of Data and Information Science)
This study investigates whether publication-centric incentive systems, introduced through the National Scientific Accreditation (ASN: Abilitazione Scientifica Nazionale) for professorships in Italy in 2012, contribute to adopting “salami publishing” strategies among Italian academics.